Recall initiation instructions influence how space and time interact in memory. - Healey, M. Karl; Gibson, Bradley S.; Uitvlugt, Mitchell G.; Gondoli, Dawn M. (Memory & Cognition, 2024)
Recent work has examined the interaction between space and time in memory search, but there is still limited understanding of this relationship. Here, we test the hypothesis that individuals can exert control over how time and space interact in response to subtle differences in task instructions. To test this hypothesis, we analyzed two experiments where participants completed two immediate free recall tasks, a verbal task involving words presented at a central location and a spatial task involving squares presented at different locations. Some participants were free to recall the words or locations spontaneously in any order they preferred. In contrast, another group was subtly biased toward temporal information by instructions to begin recall from the last presented item before recalling the remaining items in any order they wished. Replicating recent work, all conditions showed clear evidence that recall was organized along both the temporal and the spatial dimensions. Extending this work, we found that the subtle change in recall instructions increased the reliance on temporal information in the spatial recall task. Correlational analyses suggest that spatial and temporal information do not compete when participants search memory spontaneously. However, they do compete when instructions favor temporal information. These findings highlight that individuals can exert some cognitive control over how associative dimensions interact during memory search and emphasize the importance of incorporating such processes into theoretical models.